"Here’s what we really want your class to be about!": A design thinking class responds to the pandemic. - Noel, Lesley-Ann (Design and Technology Education: An International Journal, 2021)
This case study describes many changes to the curriculum of a design thinking for social innovation class at a private university in New Orleans that were prompted by the COVID-19 pandemic. The pre-COVID version of the course offered a practical, experience-based introduction to design-thinking (DT) tools and methods. Students learned to apply these tools to social innovation for collective impact through discussion, studio and fieldwork, and close collaboration with colleagues and members of the New Orleans community. The challenge during the COVID-19 pandemic was how to re-create this experiential learning while working remotely. The paper aims to demonstrate how the pandemic-related changes such as the all-remote delivery of instruction, community involvement, as well as a change in philosophy due to the racial unrest in the United States in 2020 led to a re-design of the class. The theme of the class, Sustainable Development Goal #3, “Good Health and Well-being’’ was requested by residents of New Orleans, in light of the impact of the pandemic on communities of colour in the city. Despite being a remote class, the residents were also present in the class regularly throughout the semester. The remote delivery of the class forced a need for intentional and empathetic community building among the students and with the community members. The redesigned class included conversations about race, periodic drop-in visits from community members, guest lectures from professors in other cities, feedback sessions via social media, and critiques by panels composed of community members and visiting designers from around the world.